PENERAPAN MODEL PEMBELAJARAN COOPERATIVE LEARNING (JIGSAW) TERHADAP HASIL BELAJAR SERVICE BOLAVOLI (STUDI PADA SISWA KELAS VII SMPN 2 TEMBELANG JOMBANG) - SUBIANTORO, FENDI (Jurnal Pendidikan Olahraga dan Kesehatan, 2013)
Abstract Sport physical education and healt (sport education) can be devined as one of the educational process that aims to achieve educational goals through physical activity.With penjasorkes teachers can instill the values of cooperation,tolerance,honesty, responsibility, respect for the opponent, understand themselves and habituation of healthy living. Through cooperative leaming model leaming (jigsaw) to help students leam skills ranging from basic to complex solutions, and create an effective leaming. Leaming the volleyball serve is one subject matter penjasorkes given to students, which is basically geared for students to know the basic techniques of the game of volleyball on the right, as well as student can immediately practice the material that has been tought volleyball. The research used by the researchers is experimental research, quantitative approach. Researchers can observe and examine an object in this case student, to be given leaming model of cooperative leaming (jigsaw) to serve the volleyball leaming outcomes to determine the progress of leaming outcomes volleyball. Samples from this study were student of class VII, totaling 36 students of SMPN 2 Tembelang Jombang. The purpose of this study were (1) to determine the effect of application of leaming models of cooperative leaming (jigsaw) effects the outcome of Service leaming in class VII volleyball SMPN 2 Tembelang Jombang, (2) to determaine how much influence the application of leaming models of cooperative leaming (jigsaw) to Service leaming outcomes vollyball in grade VII SMP N 2 Tembelang jombang.Results showed that the altemative hypothesis proposed in this study are accepted as thitung > ttable or thitung 13.733 > 1.684 ttable. In other words, the provision of leaming cooperative leaming (jigsaw) appeared to affect the leaming outcomes of the volleyball serve. In volleyball leaming an increase of 40.0% is significant and can be applied (generalized) to the population. Keywords: through cooperative leaming (jigsaw) to serve the vollyball.